(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
History Education greetings, Welcome to the December 2019 edition of Yesterday & Today. Unfortunately, this volume appeared a month late, at the end of January 2021. But one of the minor consequences of the COVID-19 pandemic. Minor indeed when considering the havoc, the COVID-19 pandemic has wrecked all over the world.